An automatic monitoring and control system inside greenhouse - Hassan, Md. Niamul; Noor, Ahmad Shams; Shihab Ibne Abdullah (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.